2002
DOI: 10.1002/gps.656
|View full text |Cite
|
Sign up to set email alerts
|

Access to a community aged psychiatry service by elderly from non‐English‐speaking backgrounds

Abstract: This 12-month review of referrals to an aged psychiatry community service found that nearly half were of elderly patients from NESB. The lower utilisation of the service by certain ethnic groups may reflect obstacles in their pathway to care. Alternatively, strong family networks, or a lower prevalence of mental illness in these elderly, may explain the findings in this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 4 publications
0
22
0
Order By: Relevance
“…The study provides a comprehensive analysis across primary, secondary and tertiary health services utilisation amongst Australian infants. In contrast, the previous studies in Australia mostly focused on one particular health aspect or one set of health care characteristics, or on adult populations [26-28]. …”
Section: Discussionmentioning
confidence: 99%
“…The study provides a comprehensive analysis across primary, secondary and tertiary health services utilisation amongst Australian infants. In contrast, the previous studies in Australia mostly focused on one particular health aspect or one set of health care characteristics, or on adult populations [26-28]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, migrants from Greece diagnosed with mental disorder were more likely to receive treatment than Australians; however, the opposite was found in immigrants from UK or Ireland or South East Asia [18]. Nevertheless, in general, immigrants are under-represented in the populations who utilise mental health service in Australia [108-110]. The key barriers identified are stigma and shame attached with mental illnesses [111-113].…”
Section: Mental Health Of Immigrant and Refugee Communities In Australiamentioning
confidence: 99%
“…Hasset and George (2002) showed that older people from NESBs were more likely to be poorly educated, and have a low proficiency in English. They found that interpreters were used in 78.8 per cent of patients for whom English was not their preferred first language.…”
Section: Discussionmentioning
confidence: 98%